D5.2 Report from the local promotion strategy - Hadjimitsis, Diofantos G.; Agapiou, Athos; Lysandrou, Vasiliki; Christofe, Andreas; Themistocleous, Kyriacos; Mettas, Christodoulos; Evagorou, Evagoras G.; Nisantzi, Argyro; Papoutsa, Christiana; Lasaponara, Rosa; Masini, Nicola; Krauss, Thomas; et al. (My University, 2018)
The present deliverable consists of the report on the local promotion strategy of the ATHENA project, and makes part of WP5 (Promotion of the centre locally and internationally).The strategy, was based on the promotion of the ATHENA locally with the aim to create a substantial and collaborative network, in order to sustain the Centre’s future activities.
Keywords: Promotion strategy; ATHENA project